Sacral neuromodulation for persistent faecal incontinence after laparoscopic ventral rectopexy for high-grade internal rectal prolapse - Mishra, A.; Prapasrivorakul, S.; Gosselink, M. P.; Gorissen, K. J.; Hompes, R.; Jones, O.; Cunningham, C.; Matzel, K. E.; Lindsey, I. (Colorectal Disease, 2016)
Internal rectal prolapse is recognized as an aetiological factor in faecal incontinence. Patients found to have a high-grade internal rectal prolapse on routine proctography are offered a laparoscopic ventral rectopexy after failed maximum medical therapy. Despite adequate anatomical repair, faecal incontinence persists in a number of patients. The aim of this study was to evaluate the outcome of sacral neuromodulation in this group of patients.Between August 2009 and January 2012, 52 patients who underwent a laparoscopic ventral rectopexy for faecal incontinence associated with high-grade internal rectal prolapse had persistent symptoms of faecal incontinence and were offered sacral neuromodulation. Symptoms were evaluated before and after the procedure using the Fecal Incontinence Severity Index (FISI) and the Gastrointestinal Quality of Life Index (GIQLI).Temporary test stimulation was successful in 47 (94%) of the patients who then underwent implantation of a permanent pulse generator. The median FISI score 1 year after sacral neuromodulation was lower than the median score before [34 (28-59) vs 19 (0-49); P < 0.01], indicating a significant improvement in faecal continence. Quality of life (GIQLI) was significantly better after starting sacral neuromodulation [78 (31-107) vs 96 (55-129); P < 0.01].Patients may benefit from sacral neuromodulation for persisting faecal incontinence after laparoscopic ventral rectopexy.
EVALuna2:15207